2011
DOI: 10.1083/jcb.201105136
|View full text |Cite
|
Sign up to set email alerts
|

Sticky/Citron kinase maintains proper RhoA localization at the cleavage site during cytokinesis

Abstract: Regulated RhoA localization at the cleavage site is mediated by the Sticky/Citron kinase and ensures RhoA’s proper activation and appropriate contractile ring dynamics during cytokinesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
105
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(113 citation statements)
references
References 25 publications
7
105
1
Order By: Relevance
“…Previous results indicated that the primary function of CIT-K, conserved from insects to mammals, is to promote the stability and the maturation of midbody before abscission. 15,[23][24][25] To assess whether this function may involve the stabilization of midbody microtubules, we measured the ratio of acetylated versus tyrosinated α-tubulin at the midbody of control cells and of cells lacking CIT-K. 28 Indeed, dynamic microtubules contain a relatively high amount of α-tubulin tyrosinated at its carboxyterminus, whereas stable microtubules show a high content of α-tubulin acetylated at the K40 residue. 29 We studied two cellular models characterized by different sensitivity to CIT-K loss and by different physiological relevance: cultures of proliferating neocortical neuronal progenitors obtained from control or from Cit-K knockout mice at embryonic day (E)12.5 and HeLa cells depleted of CIT-K by RNAi.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous results indicated that the primary function of CIT-K, conserved from insects to mammals, is to promote the stability and the maturation of midbody before abscission. 15,[23][24][25] To assess whether this function may involve the stabilization of midbody microtubules, we measured the ratio of acetylated versus tyrosinated α-tubulin at the midbody of control cells and of cells lacking CIT-K. 28 Indeed, dynamic microtubules contain a relatively high amount of α-tubulin tyrosinated at its carboxyterminus, whereas stable microtubules show a high content of α-tubulin acetylated at the K40 residue. 29 We studied two cellular models characterized by different sensitivity to CIT-K loss and by different physiological relevance: cultures of proliferating neocortical neuronal progenitors obtained from control or from Cit-K knockout mice at embryonic day (E)12.5 and HeLa cells depleted of CIT-K by RNAi.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the previous studies implicating CIT-K in actindependent midbody stabilization, 23,25,53 these results add strong support the notion that CIT-K plays a crucial role in the crosstalk between actin and microtubules responsible for the maturation of midbody that precedes abscission. [23][24][25]54 The activity of CIT-K on microtubule stability is most likely independent from the reported interaction between CIT-K and KIF14. Indeed, although KIF14 may be functionally implicated in crosslinking midbody microtubules via its interaction with PRC1, 25 it does not seem to affect their stability (Figures 2a and b).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Two contractile ring proteins play this role: anillin and citron kinase (CIT-K). Both proteins associate with actin and myosin and interact directly with RhoA, although they do not seem to behave as canonical RhoA effectors (Madaule et al 1995;Piekny and Glotzer 2008;D'Avino 2009;Bassi et al 2011). In particular, CIT-K is required for proper RhoA localization, indicating that it behaves more like a RhoA regulator (Bassi et al 2011;Gai et al 2011).…”
Section: Animal Cell Cytokinesismentioning
confidence: 99%
“…In addition, a carbohydrate-binding protein Nessun Dorma (NESD) binds centralspindlin and plays a role in late cytokinesis (Montembault et al, 2010). Another midzone factor, citron kinase, which regulates late cytokinesis events through Rho (Bassi et al, 2011;Gai et al, 2011), depends on KIF14 for its midzone localisation (Gruneberg et al, 2006).…”
Section: Interactions Between Midzone Organisers and Their Upstream Amentioning
confidence: 99%